2021 43rd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2021
DOI: 10.1109/embc46164.2021.9630200
|View full text |Cite
|
Sign up to set email alerts
|

Hand Temperature Is Not Consistent With Illusory Strength During the Rubber Hand Illusion

Abstract: The rubber hand illusion is known to invoke a sense of ownership of a rubber hand when a person watches the stroking of the rubber hand in synchrony with their own hidden hand. Quantification of the sense of ownership is traditionally performed with the rubber hand illusion questionnaire, but the search for reliable physiological measurements persists. Skin temperature has been previously suggested and debated as a biomarker for ownership. We investigated hand temperature as a measure of rubber hand illusory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The RHI has been used to investigate the link between internal representation of the body and various autonomic indices. Synchronous stroking has been reported to decrease participants’ real hand skin temperature ( Llobera et al, 2013 , Moseley et al, 2008 , Tieri et al, 2018 , Tsakiris et al, 2011 ), even though the consistency of such finding is currently not confirmed by other studies ( de Haan et al, 2017 , Rohde et al, 2013 ) ( Lang et al, 2021 ; Roel Lesur, Weijs et al, 2020 ). Furthermore, an increase of histamine reactivity was also observed by comparing wheal dimension after histamine injection on the tested and contralateral arm ( Barnsley et al, 2011 ).…”
Section: Autonomic Correlates Of the Rhimentioning
confidence: 83%
“…The RHI has been used to investigate the link between internal representation of the body and various autonomic indices. Synchronous stroking has been reported to decrease participants’ real hand skin temperature ( Llobera et al, 2013 , Moseley et al, 2008 , Tieri et al, 2018 , Tsakiris et al, 2011 ), even though the consistency of such finding is currently not confirmed by other studies ( de Haan et al, 2017 , Rohde et al, 2013 ) ( Lang et al, 2021 ; Roel Lesur, Weijs et al, 2020 ). Furthermore, an increase of histamine reactivity was also observed by comparing wheal dimension after histamine injection on the tested and contralateral arm ( Barnsley et al, 2011 ).…”
Section: Autonomic Correlates Of the Rhimentioning
confidence: 83%
“…Similar ndings were obtained in other studies [8][9][10] . However, many other studies found no modulation of the real hand temperature during the RHI [11][12][13][14][15] . Since reports on the hand temperature change during the RHI seemed inconsistent, it was important to clarify whether a physiological change such as decreased hand temperature was a suitable biomarker for the illusion strength.…”
Section: Introductionmentioning
confidence: 87%